Propofol Infusion Syndrome in Adults: A Clinical Update - Aibek E. Mirrakhimov; Prakruthi Voore; Oleksandr Halytskyy; Maliha Khan; Alaa M. Ali (Critical Care Research and Practice)
Propofol infusion syndrome is a rare but extremely dangerous complication of propofol administration. Certain risk factors for the development of propofol infusion syndrome are described, such as appropriate propofol doses and durations of administration, carbohydrate depletion, severe illness, and concomitant administration of catecholamines and glucocorticosteroids. The pathophysiology of this condition includes impairment of mitochondrial beta-oxidation of fatty acids, disruption of the electron transport chain, and blockage of beta-adrenoreceptors and cardiac calcium channels. The disease commonly presents as an otherwise unexplained high anion gap metabolic acidosis, rhabdomyolysis, hyperkalemia, acute kidney injury, elevated liver enzymes, and cardiac dysfunction. Management of overt propofol infusion syndrome requires immediate discontinuation of propofol infusion and supportive management, including hemodialysis, hemodynamic support, and extracorporeal membrane oxygenation in refractory cases. However, we must emphasize that given the high mortality of propofol infusion syndrome, the best management is prevention. Clinicians should consider alternative sedative regimes to prolonged propofol infusions and remain within recommended maximal dose limits.